Islamic home financing in Pakistan: a SEM-based approach using modified TPB model - Ali, Muhammad; Syed, Ali Raza; Puah, Chin Hong; Mohd Zaini, Abd Karim (Routledge, 2015)
The present study attempts to examine the Islamic home financing using the modified theory of planned behavior model (TPB). Sample data of 375 are conveniently drawn from walk-in customers of Islamic banks located in the biggest city Karachi. This study employed both exploratory factor analysis and confirmatory factor analysis to confirm the validity and reliability of the measurement model. The modified theoretical framework was examined by applying the structural equation modeling using frequently reported goodness-of-fit indices. The findings indicate that the original constructs of TPB model, attitude (ATT), subjective norm (SN) and perceived behavioral control has a positive and significant impact on the customer intention to use Islamic home financing. Furthermore, ATT is found to be the most influential factor in determining the customer intention toward Islamic home financing. On the other hand, we introduced two new factors, pricing on home financing (PHF) and religious belief (RB), which proved their presence in the TPB model by showing a significant impact on the customer intention to use the facility of home financing. In addition, PHF has a negative impact while religious belief has a positive relationship with the customer intention to use Islamic home financing in Pakistan. This study also suggests that the standard TPB model is successfully modified by introducing PHF and RB factors. Therefore, Islamic bank managers should consider this study to promote the Islamic home financing facility in Pakistan.